Transport enhancement from incoherent coupling between one-dimensional quantum conductors - Mendoza-Arenas, J; Mitchison, M; Clark, SR; Prior, J; Jaksch, D; Plenio, M (Institute of Physics Publishing, 2014)
We study the non-equilibrium transport properties of a highly anisotropic twodimensional lattice of spin?1/2 particles governed by a Heisenberg XXZ Hamiltonian. The anisotropy of the lattice allows us to approximate the system at finite temperature as an array of incoherently coupled one-dimensional chains. We show that in the regime of strong intrachain interactions, the weak interchain coupling considerably boosts spin transport in the driven system. Interestingly, we show that this enhancement increases with the length of the chains, which is related to superdiffusive spin transport. We describe the mechanism behind this effect, compare it to a similar phenomenon in single chains induced by dephasing, and explain why the former is much stronger. © 2014 IOP Publishing Ltd and Deutsche Physikalische Gesellschaft.